2005
DOI: 10.1002/sia.2101
|View full text |Cite
|
Sign up to set email alerts
|

Cross sections for electron interactions in condensed matter

Abstract: The fundamental components of Monte Carlo algorithms for the simulation of electron transport in matter are the differential and total cross sections for the relevant interaction mechanisms. We present different theoretical models and approximations to compute these cross sections for elastic scattering, inelastic collisions and bremsstrahlung emission of electrons with kinetic energies larger than about 100 eV. We limit our considerations to those models that are broadly applicable and suited for efficient ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…It can be shown that Eqs. (25) and (26) provide an ''exact'' expression for the screened interaction between a test-charge and an electron; equivalent to the so-called ''GWC'' approximation of many-body perturbation theory for the electron selfenergy (87). In the case now where both test-charges are substituted by electrons, no exact expression exists but an approximate expression is provided by the KukkonenOverhauser (KO) theory (88).…”
Section: Vertex Correctionmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be shown that Eqs. (25) and (26) provide an ''exact'' expression for the screened interaction between a test-charge and an electron; equivalent to the so-called ''GWC'' approximation of many-body perturbation theory for the electron selfenergy (87). In the case now where both test-charges are substituted by electrons, no exact expression exists but an approximate expression is provided by the KukkonenOverhauser (KO) theory (88).…”
Section: Vertex Correctionmentioning
confidence: 98%
“…(24,25) and references therein]. The idea behind such models is that the dielectric function at the optical limit (i.e., at zero-momentum transfer) can be determined from experimental data, while extrapolation to non-zero momentum transfer, where experimental data are limited (or nonexisting), may be provided by theoretically motivated so-called extension algorithms (26).…”
mentioning
confidence: 99%
“…The calculation of electron IMFP using any of the standard models discussed earlier is carried out using the non‐relativistic expression of the Born approximation Σmodel=2πυ20.12emtruedωtruedkknormalInormalmsans-serif1ε(),ωkmodel where υ is the velocity of the incident electron, normalInormalm+11εωkmodel is the ELF determined by the RH, or Penn (FPM or SPM) or MELF model and Σmodelprefix−1 equals the corresponding IMFP. It is important to recognize that, as long as normalInormalm1εωkmodel is only an approximation to the ‘true’ ELF of the material, Eqn will yield an approximation to the IMFP of the Born approximation.…”
Section: The ‘Standard’ Modelsmentioning
confidence: 99%
“…[27] Because of the aforementioned properties, the use of the MELF model is expanding. [28][29][30][31] The calculation of electron IMFP using any of the standard models discussed earlier is carried out using the non-relativistic expression of the Born approximation [32] Σ model ¼ 2…”
Section: Melf Modelmentioning
confidence: 99%
“…Over the past decades several TS codes have been developed in the context of microdosimetry and radiobiological modeling of cellular effects, e.g., NOREC [6], PARTRAC [7], KURBUC [8], RETRACKS (RITRACKS) [9], Geant4-DNA [10], among others [11]. The main problem with TS models is that they contain a high-degree of detail and, therefore, they are difficult to develop [12]. As a result, TS models are commonly tailored to a single medium (e.g., water) which prohibits their use in general-purpose codes [13].…”
Section: Introductionmentioning
confidence: 99%